Validity and reliability of strategy metrics to assess countermovement jump performance using the newly developed My Jump Lab smartphone application - Bishop, C.; Jarvis, P.; Turner, A.; Balsalobre-Fernandez, C. (Journal of Human Kinetics, 2022)
The aim of the present study was to analyse the validity and reliability of the newly developed My Jump Lab smartphone app, which includes the option to calculate time to take-off and the reactive strength index modified (RSI_Mod - calculated as jump height divided by time to take-off), in addition to jump height. Twenty-seven postgraduate sport science students attended a single test session and performed three maximal effort countermovement jumps (CMJ) on twin force plates, whilst concurrently being filmed using the app. Results showed no significant differences in jump height between measurement methods (g = 0.00) or RSI_Mod (g = -0.49), although a significant difference was evident for time to take-off (g = 0.68). When a correction factor was applied to time to take-off data, no meaningful differences were evident (g = 0.00), which also had a knock-on effect for RSI_Mod (g = 0.10). Bland-Altman analysis showed near perfect levels of agreement for jump height with a bias estimate of 0.001 m, whilst time to take-off reported a bias estimate of 0.075 s initially and, 0.000 s once the correction factor was applied. For RSI_Mod, bias estimate was initially -0.048, and 0.006 once calculated with the corrected time to take-off data. Pearson`s r correlations were: 0.98 for jump height, 0.81 for time to take-off, and 0.85 for RSI_Mod. Based on the findings from the present study, and with the inclusion of the newly embedded correction factor, My Jump Lab can now be used as both a valid and reliable means of measuring time to take-off and RSI_Mod in the CMJ.